Increased antitumor efficiency and reduced negative side effects in laboratory mice of 4-thiazolidinone derivatives in complexes with PEG-containing polymeric nanocarrier - Kobylinska, L.I.; Skorohyd, N.R.; Klyuchivska, O.Yu.; Mitina, N.E.; Zaichenko, A.S.; Lesyk, R.B.; Zimenkovsky, B.S.; Stoika, R.S. (Інститут молекулярної біології і генетики НАН України, 2018)
Aim. To study an anticancer activity and to measure cytological and enzymatic indicators of general toxicity of 4-thiazolidinone-based compounds (Les-3288, Les-3833) in the NK/Ly lymphoma grafted to BALB/C mice. Methods. BALB/C mice were implanted with the ascitic NK/Ly lymphoma and treated for 14 days with 4-thiazolidinone derivatives – Les-3833 (2.5 mg/kg of bodyweight), Les-3288 (5 mg/kg of bodyweight), a complex of Les-3833 with the polymeric nanocarrier Les-3833+PNC (2.5 mg/kg of bodyweight) in water, and doxorubicin (1 mg/kg of bodyweight) used as a positive control. The lymphoma development was monitored by measuring the amount of ascitic fluid in the treated mice. The effects of the applied compounds were checked after 35 days of tumor growth. Results. A distinct decrease in the amount of the ascite fluid with lymphoma cells was revealed in the treated mice, while a 1.5-fold increase of its amount was detected in the untreated mice of control group. The 4-thiazolidinone derivatives demonstrated much less toxicity, and erythrocytes count stayed normal after 21 days of animal treatment. The development of NK/Ly lymphoma led to an increase in the neutrophils number, while the applied anticancer compounds reduced it significantly. Les-3833 and Les-3288 did not affect the number of lymphocytes over the normal level. The activity of aspartate and alanine aminotransferases in blood serum was elevated on the 14 day of treatment, and returned to the normal level on the 21 day. Conclusion. Novel 4-thiazolidinones Les-3833 and Les-3288 are effective in the treatment of NK/Ly lymphoma grafted to BALB/C mice. These derivatives induced had limited negative side effects in the treated mice.